RESISTENSI Staphylococcus aureus ASAL SUSU SAPI PERAH DI BALAI BESAR PEMBIBITAN TERNAK UNGGUL (BBPTU) BATURRADEN TERHADAP BERBAGAI ANTIBIOTIK - , SITI AMINAH; , Prof. Dr. drh. Siti Isrina Oktavia Salasia ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Staphylococcus aureus is a major bacterial pathogen causing subclinical mastitis on dairy cow. Subclinical mastitis is usually treated by using antibiotics. Improper use of antibiotics causes bacterial resistance to certain antibiotics. This study aimed to determine the resistance of S. aureus isolated from milk of dairy cows against methicillin, erythromycin, doxcycycline , gentamycin, ciprofloxacin and penicillin.. 17 Staphylococcus aureus isolated from milk of dairy cows were used in this study. Identification of S. aureus based on the growths of bacteria the Todd- Hewit Broth (THB), mannitol salt agar (MSA), blood agar plate (PAD), Gram staining, catalase and coagulase test. Sensitivity test against antibiotics were done by using the media of MÃ¼ller Hinton agar (MHA) by Disc Diffusion of Kirby- Bauer test. The kinds of antibiotics used in the sensitivity tests were methicillin 5 Î¼g, erythromycin 15 Î¼g , doxycycline 30 Î¼g, gentamycin 10 Î¼g, ciprofloxacin 5 Î¼g and penicillin G 10 Î¼g. The measurements of inhibition zones on the MÃ¼ller Hinton against various antibiotics were compared to the standard Kirby-Bauer table. The results showed that all Staphylococcus aureus isolates were resistance to methicillin (5,88%), penicillin G (35,30%), erythromycin (0%), doxycycline (0%), gentamycin (5,88%) and ciprofloxacin (0%). From the research result can be concluded that subclinical mastitis caused by S. aureus in dairy cow in Baturraden can be treated use erythromycin, doxycycline and ciprofloxacin.